Industrial proteomics : applications for biotechnology and pharmaceuticals - Figeys, Daniel (Wiley Interscience, 2005)
This book covers both basic elements and the state--of--the--art in applications of proteomics. The first section gives an introduction to the field, from differential approaches to functional proteomics, including yeast two--hybrid, mass spectrometry, mapping of post--translational modifications, and NMR spectroscopy. The second section offers a complete picture of industry studies in proteomics for human health and biotechnology applications. The final section addresses the future, looking at the most promising areas such as protein arrays and the integration of genomic and proteomic tools.